Bilateral Purtscher’s retinopathy associated with acute pancreatitis – case report - Korporowicz, Danuta; Sobecki, Roman; Żyszko, Justyna; Sawicka, Elżbieta (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The project’s aim is to report a case of Purtscher’s retinopathy associated with acute pancreatitis. During the treatment gradual improvement of visual acuity and retina condition have been observed. In the report, the actual views on the pathogenesis of this disease have been discussed.